An easy method for the clear detection of beige fat UCP1 by Western blotting - Park, Min-Jung (Adipocyte, 2019)
Beige adipocytes, which consume energy mainly in an uncoupling protein 1 (UCP1)-dependent manner, are risen in white adipose tissue (WAT) depots. Since beige adipocyte development is gaining attention as a potential strategy for conquering obesity, worldwide researchers are making efforts to study its biological aspects. However, assessing UCP1 protein levels in beige adipocytes is challenging because of the high level of lipid contaminants in WAT. This study showed that an acetone precipitation method had advantages over conventional methods for eliminating lipid contaminants, achieving clear Western blot bands for WAT proteins, especially UCP1. Our results suggest that the acetone precipitation cleaning method could be useful for the clear analysis and precise evaluation of WAT proteins.